Researching code-switching in teacher classroom discourse : Questioning the sufficiency of informant reports - Then, David Chen-On; Ting, Su Hie (The International Journal - Language Society and Culture, 2011)
This study examined the functions of code-switching in teacher classroom discourse using informant reports and direct observations to find out whether teachers were aware of their use and purposes of code-switching. The participants of the study were 18 teachers teaching Forms 1 and 2 in three Malaysian secondary schools. Non-participant observations were carried out and the lessons were audiotaped. Semi-structured interviews were subsequently conducted to obtain the teachers’ reports of their code-switching practices and reasons for code-switching. Analysis of the interview transcripts showed that code-switching was mainly for the purposes of addressing students’ problems in understanding terms and instructions, either to avert or solve comprehension problems. Analysis of the teacher classroom discourse using Gumperz’s (1982) semantic model of code-switching functions showed that explanations of unfamiliar terms involved quotations and proper nouns. For ensuring clarity when giving instructions, the teachers code-switched for reiteration and message qualification, and performed situational code-switching. These code-switching functions account for 84.15% of the 246 instances of code-switching identified in the ten hours of teacher classroom discourse. The mismatches from the triangulation of the informant reports and teacher classroom discourse provide empirical support for the notion that code-switching is largely a sub-conscious process. The findings point to the insufficiency of informant reports in researching how code-switching is used to facilitate students’ learning.